Human Mobility Datasets in the Complex Metro System of Shanghai - Peiyan Sun; Jinming Yang; Zongyuan Huang; Shaoyu Huang; Shengyuan Xu; Weipeng Wang; Wenxuan Guo; Yuting Feng; Xi Zhai; Tao Yang; Xiaokang Yang; Yaohui Jin; et al. (Scientific Data)
Abstract The growing role of metro systems in urban mobility calls for high-quality metro transit datasets. Derived from over 700 million smart card records, an open-sourced, city-scale metro flow dataset was constructed, covering the period of May-August 2017 and 302 metro stations in Shanghai, China. The in-out flow counts of each station and OD flow between stations were offered at a 10-minute temporal resolution. By leveraging the mobility patterns of each passenger, metro flows were categorized into commuting flows, home-based-other flows, and none-home-based flows, providing a more comprehensive perspective towards urban mobility dynamics. Supplemental metadata, including station attributes, network topology, and meteorological records further support potential applications. This city-scale metro flow dataset could be utilized in advancing research in transportation modeling, spatio-temporal data mining, and urban mobility analysis.